Miscible-blend polysulfone/polyimide membrane for hydrogen purification from palm oil mill effluent fermentation - Abd Hamid, Mohd Azam; Chung, Ying Tao; Rohani, Rosiah; Junaidi, Mohd Usman Mohd (Elsevier, 2019)
The biogas produced from the anaerobic fermentation of palm oil mill effluent (POME) contains equal amount of H2 and CO2, in which the biohydrogen (bioH2) is a prospective source of renewable energy. Therefore, the determination of an efficient H2 purification technique has been a major concern. Membrane separation technology is highly recommended due to its excellent purification performance with high permeation of H2 and H2/CO2 selectivity. Polymer blending is a favourable approach due to its simplicity to refine membrane inner structural properties by combining different polymers with complementary features. In this study, the synthesized polysulfone-polyimide (PSf/PI) membrane is an alternative polymeric membrane practicable for H2/CO2 separation due to its outstanding permeation properties, enhanced membrane properties as well as improved tolerance to plasticizing gases. The effect of evaporation time on PSf/PI membranes was further investigated and was thoroughly characterized by FTIR, TGA, DSC and SEM. The miscibility of the PSf/PI blending was proven by DSC with the detection of only single glass transition temperature value. The highest permeability of both H2 and CO2 gas were presented by PSf/PI-60 membrane with 348 GPU and 86 GPU, respectively, H2/CO2 selectivity of 4.4 and H2 purification efficiency of 80%. Hence, PSf/PI membrane is a high potential candidate with inherent properties for H2/CO2 separation from POME fermentation.